Influence of a Biodegradable Synthetic Hydrogel Used as a Guided Bone Regeneration Membrane in Sinus Floor Augmentation - BAYRAM, FERİT; GÖÇMEN, GÖKHAN; ÖZKAN, YAŞAR (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objective: The purpose of this study is to compare the clinical, histological, and radiological aspects of the polyethylene glycol (PEG) hydrogel membrane and the standard collagen membrane in sinus floor augmentation procedures when the same bone filling material is used. Methods: Fourteen patients (5 men and 9 women) were included in this prospective cohort study. Twenty sinus floor augmentation surgeries were randomly divided into two groups: the study group (n=10) and the control group (n=10). An anorganic bovine graft (Bio-Oss (R), Geistlich Pharma AG, Switzerland) was used in all patients as the bone-filling material. As a protective membrane, a collagen membrane (Bio-Gide (R), Geistlich Pharma AG, Switzerland) was used in the control group patients, as well as a PEG membrane (Membragel (R), Institut Straumann AG, Switzerland) in the study group. After 6 months, the samples were collected during implant site preparation for histopathological evaluation. Results: There were no statistically significant differences between the control and the study groups in the histological examination regarding the soft-to-hard tissue ratio. There was no statistically significant difference between the control and study groups in the resonance frequency analysis measurements at different times. No postoperative inflammation or exposure of the membrane was observed in any of the patients. The visual analogue scale scores measured at different times also showed no significant difference. Conclusion: A PEG membrane can be used as an alternative to a collagen membrane as a barrier in sinus floor augmentation procedures.
Keywords: Sinus floor augmentation; bone substitutes; guided tissue regeneration; polyethylene glycol; ANORGANIC BOVINE BONE; HISTOLOGIC EVALUATION; POSTERIOR MAXILLA; IMPLANT STABILITY; AUTOGENOUS BONE; CLINICAL-TRIAL; BIO-OSS; DEFECTS; GRAFTS; ELEVATION